THE INFLUENCE OF ORGANIZATIONAL, INTERACTION AND COMMUNICATION, COSTS AND WAITING TIMES ON PATIENT SATISFACTION AT XYZ HOSPITAL IN NORTH MINAHASA - Pricillia Caroline Mantiri; Pauline Henriette Pattyranie Tan (Media Bina Ilmiah, 2025)
In a strategy to increase the number of patients and also improve the quality of services, health service providers compete with each other to improve and improve their performance in selling health services. XYZ Hospital in North Minahasa is a private hospital that has been operating since 2020. The number of patient visits at XYZ Hospital in North Minahasa continues to increase considering that this hospital is the only type B private hospital in the North Minahasa area. However, patient satisfaction at XYZ Hospital in North Minahasa is not in line with the increase in patients. This study aims to determine the factors that influence patient satisfaction at XYZ Hospital in North Minahasa. This research uses quantitative research methods using questionnaires to 170 outpatient insurance patients. The results of this research are that patient demographic variables, organizational factors, interaction between patients, attention and emotional support, communication and information and waiting time have a positive and significant influence on patient satisfaction. Meanwhile, health costs have a negative and insignificant influence on patient satisfaction. So, hospitals should implement strategies to increase patient satisfaction by creating a culture of safety to increase patient satisfaction at XYZ Hospital in North Minahasa